Strategy for Handling Victims of Sexual Violence and Bullying by Unit Layanan Terpadu Kekerasan Seksual dan Perundungan (ULTKSP) Faculty of Vocational University of Brawijaya - Susilowati, Susilowati - (Journal of Innovation and Applied Technology, 2023)
The phenomenon of sexual violence and bullying that occurs on campus is often carried out by educated people, both fellow students, lecturers and education staff. With the increase in sexual violence that occurs in tertiary institutions, it will directly or indirectly have an impact on the less than optimal implementation of the Tridharma of Higher Education and reduce the quality of higher education. University of Brawijaya established Unit Layanan Terpadu Kekerasan Seksual dan Perundungan (ULTKSP), a unit that functions as an integrated service provider for victims of Sexual Violence and/or Bullying which is managed by University of Brawijaya and carried out by the Faculty, Postgraduate and Study Programs Outside the Main Campus.  The strategy used to handle victims of sexual violence and/or bullying, namely services; Inspection; Protection; Recovery; Accompaniment; Prosecution of Perpetrators and Supervision.